Conviction : Finitude, Freedom, and the Hermeneutics of Selfhood - Portocarrero, Maria Luísa; Umbelino, Luís António; Wiercinski, Andrzej (Hermeneutics in Enactment. International Research in Hermeneutics and Phenomenology, 2025)
This volume offers a fresh perspective on the quest for authentic self-understanding, addressing thought-provoking questions of identity, belief, and existential reflection. In a hermeneutic journey it delves into how deeply held convictions define personal identity, guiding decisions, and actions within the limits of human existence. By acknowledging life's finitude, we gain deeper insight into our freedom as the power to pursue meaningful choices aligned with our convictions. Promoting the culture of asking questions, the authors unfold the complex interaction of conviction, existential limits, and freedom in forming the self.